The genome project in biomedical literature within four countries in latin america - Lolas Stepke, Fernando; Rodríguez Yunta, Eduardo; Valdebenito Herrera, Carolina (Acta Bioethica, 2004)
The present reflection refers to data obtained about the social representations of genomic research and its applications through the review of local literature written by biomedical researchers in four Latin American countries: Argentine, Chile, Mexico and Peru. Several issues are addressed, such as: little access to prevention and therapeutic methods related to genomic medicine in Latin America; the risk associated to genetic modifications in human beings; lack of equity in the access to health benefits; control by biotechnological companies; commercialization of gene sequences through patents which leads to commercial exploitation of underdeveloped countries; the possibility of physical or psychological damage in the way of stigmatization or genetic discrimination; the possibility of genetic modifications or abortion for eugenic reasons; the necessity of safeguarding confidentiality; the little participation of indigenous communities in the studies done on their DNA, sometimes without proper informed consent; the necessity of legal regulation to prevent the pathway towards enhancement of genetic modifications or reproductive human cloning, and of regulating access to genetic information.